Medical methods of abortion using lowest effective dose of mifepristone and misoprostol: case study of 100 women - Anjum, Mehvish; D., Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical abortion or Medical Methods of abortion (MMA) (or Chemical abortion) is defined as “the non-surgical way of termination of termination of pregnancy by a drug or combination of drugs”. With introduction of MMA there has been a steep rise in abortion related complications due to irrational use of these drugs. This study is undertaken using lowest effective dose of mifepristone and misoprostol in 100 women willing for termination of pregnancy with period of gestation <49 days to study the efficacy, side effects and failure rate. Present study emphasizes on using MMA by proper selection of patient, adhering to proper schedule under provision of MTP Act (counselling, consent, examination, confirmation of pregnancy, prescription by a registered medical practioner) in order to enhance efficacy and avoid complications. Methods: Prospective Clinical Study consist of use of single dose of 200mg of mifepristone orally followed by misoprostol (400µg) by vaginal route for terminating pregnancy in ≤49 days of gestation. Statistical analysis done by Chi square test. Results: In this study, success rate i.e. complete abortion without requiring surgical procedure was 96%and failure rate was 4%. Nausea (56%) is the most common side effect of Mifepristone. Chills (33%) is the most common side effect of Misoprostol. Mean Induction Abortion Interval is 2.17±1.2 hrs. Mean Duration of Bleeding is 7.79±4.42 days. Conclusions: Medical abortion is a promising method of early abortion in a developing country like India as it requires no technical skills and manpower with a good safety profile.